2004
DOI: 10.1108/14777830410540126
|View full text |Cite
|
Sign up to set email alerts
|

Environmental management in Brazilian companies

Abstract: The survival of an organisation today depends directly on its capacity to be efficient and competitive. Growing transformations in the world economy impose new variables on the productive process. Environmental management is one of these variants, which brings in itself a series of opportunities and risks. An environmental management system (EMS) allows an organisation to permanently control the effects of the productive process on the environment. In Brazil, the adoption of this new approach still finds certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 1 publication
0
16
1
1
Order By: Relevance
“…Indeed, Chavan (2005) documented that the implementation of EMSs through the certification ISO 14001 helps firms achieve the following results: lowering their environmental impact, optimizing the efficient use of resources, lowering waste, building a good corporate image, raising the awareness of the environment and augmenting the corporate profit through more efficient operations. Da Silva and de Medeiros (2004) found that environmental management permits the company to better its environmental performance, lower its costs, improve its image with the public, regulators and investors; restrain pollution, save resources and find new customers and new markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, Chavan (2005) documented that the implementation of EMSs through the certification ISO 14001 helps firms achieve the following results: lowering their environmental impact, optimizing the efficient use of resources, lowering waste, building a good corporate image, raising the awareness of the environment and augmenting the corporate profit through more efficient operations. Da Silva and de Medeiros (2004) found that environmental management permits the company to better its environmental performance, lower its costs, improve its image with the public, regulators and investors; restrain pollution, save resources and find new customers and new markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study has some limitations. First, it has been observed that the existing production facilities and practices in most of the industrial companies, particularly production processes, need to be enhanced so that they become more environmentally friendly (Sena da Silva & Dumke de Medeiros, 2004). In this regard, Sena da Silva and Dumke de Medeiros detected that companies belonging to the chemical industry have a strong concern with the impacts that this sector can cause to the environment.…”
Section: Limitations and The Direction Of Future Researchmentioning
confidence: 99%
“…In addition, beyond the direct savings, a growing proportion of consumers rewards businesses that attend to environmental issues through their business practices (Menon & Menon 1997). However, Sena da Silva and Dumke de Medeiros (2004) suggested that companies that implement environmental initiatives could not know for certain whether these plans are designed to help companies achieve their business goals. Theyel (2000), for instance, found that firms have not been able to improve their environmental performance as expected, primarily because of the differences between business objectives and environmental management objectives.…”
mentioning
confidence: 99%
“…Pelo fato dos riscos ambientais representarem um dos maiores e mais urgentes desafios que a humanidade enfrenta, a responsabilidade ambiental tornou-se uma das temáticas mais importantes (GILL, 2012), que tem levantado discussões nas esferas social, econômica e política nas últimas décadas, para sensibilizar gestores organizacionais a integrarem esforços em suas estratégias de negócios pautadas na conservação e no uso eficiente de recursos naturais, a fim de, entre outros benefícios, obter vantagem competitiva (SILVA;MEDEIROS, 2004;SINDHI;KUMAR, 2012).…”
Section: Introductionunclassified